Does independent directors' monitoring affect reputation? Evidence from the stock and labor markets - Jun Du; Qingchuan Hou; Xuesong Tang; Yiwei Yao (China Journal of Accounting Research, 2018)
Using novel data on independent directors' opinions in China, we investigate the stock and labor market effects prompted by independent directors publicly saying "no" to major board decisions. We find that the market reacts negatively to modified director opinions, but positively to firms interlocked with the directors who said "no." We further find substantial turnover and decline in board seats after independent directors issue modified opinions. Overall, we identify a dilemma in China whereby the labor market does not reward vigilant directors for standing up to firm insiders, although investors add a premium to effective board monitoring.
Keywords: 650; Corporate Governance; Eigentümerstruktur; Führungsorganisation